Membangun Identitas Lokal Dalam Era Globalisasi Untuk Melestarikan Budaya dan Tradisi Yang Terancam Punah - Sari, Tri Yunita; Kurnia, Heri; Khasanah, Isrofiah Laela; Ningtyas, Dina Nurayu (Universitas Cokroaminoto Yogyakarta, 2022)
Globalization is the process by which the world becomes increasingly connected through the exchange of information, trade and interaction between countries. The impact on local culture and traditions is significant. Globalization brings changes in lifestyles, consumer preferences, and cultural influences from other countries. The research method that can be used in articles is literature study. Literature study will involve systematic collection and analysis of various relevant literature sources, such as books, journal articles, research reports, and other related documents. This research will focus on identifying and understanding the challenges and consequences of globalization on local culture and traditions that have the potential to threaten their survival. The results of the study show that by increasing understanding and respect for local culture and traditions through the educational curriculum, integrating local cultural and traditional materials into learning in schools, and involving the community in the educational process to pass down cultural values ​​and traditions, we can succeed in preserving and strengthening local identity in facing the ever-evolving challenges of globalization.